Mitigating aluminum toxicity and promoting plant resilience in acidic soil with Penicillium olsonii TLL1 - Dhandapani, Savitha; Sng, Yee Hwui; Agisha, Valiya Nadakkakath; Suraby, Erinjery Jose; Park, Bong Soo (Frontiers in Plant Science, 2024)
Aluminum (Al), prevalent in the crust of the Earth, jeopardizes plant health in acidic soils, hindering root growth and overall development. In this study, we first analysed the Al- and pH- tolerance of the Penicillium olsonii TLL1 strain (POT1; NRRL:68252) and investigated the potential for enhancing plant resilience under Al-rich acidic soil conditions. Our research illustrates the extraordinary tolerance of POT1 to both high Al concentrations and acidic conditions, showcasing its potential to alleviate Al-induced stress in plants. Metabolite analysis revealed that POT1 detoxifies Al through organic acid-dependent chelation mechanisms, significantly reducing Al stress in Arabidopsis and Pak Choi plants. Consequently, plant growth conditions improved, and the Al content in plant tissues decreased. Transcriptome analysis indicated that POT1 treatment downregulates genes associated with Al and oxidative stress such as MATE, ALS3, NIP1–2 and several peroxidases, highlighting its effectiveness in lessening Al-induced damage. Comparative assessments highlight the superior performance of POT1 compared to other Al-tolerant Penicillium species, attributed to its ability to thrive in diverse pH levels and effectively detoxify Al. These findings position POT1 as a promising agent for enhancing crop resilience in Al-compromised acidic soils, offering new avenues for promoting plant health and bolstering food security through increased crop yield and safety.